Comparative Study of the Nutrient Content of Fish and Shell Fish* - MUKUNDAN, M K; RADHAKRISHNAN, A G; JAMES, M A; NAIR, M R (Fishery Technology, 2017)
The amino acid, mineral and proximate composition of mullet (Mugil oeur), mackerel (Rastrelliger kanagurta), crab (Scylla serrata) and prawn (Penaeus indicus) are reported. The data are used for comparing the nutritional quality of the fish and shell fish. Further, the amino acid composition is screened for their adequacy to meet the FAO/WHO recommended pattern of essential amino acids.